2018
DOI: 10.15587/1729-4061.2018.140324
|View full text |Cite
|
Sign up to set email alerts
|

Design of the composition of alkali activated portland cement using mineral additives of technogenic origin

Abstract: Робота охоплює результати розробки складів цементу і технології виробництва для поширених цементних систем «портландцементний клінкермінеральні добавки-лужний активатор-водоредикуюча добавка», що містять більше 60 % за масою мінеральних добавок. Добавки обрано з групи: доменний гранульований шлак, золи теплових електростанцій (зола виносу та відвальні золи) та червоний шлам (відходи глиноземного виробництва). Актуальність роботи пов'язана із необхідністю покращення цілої низки показників, що обмежують широке з… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Environmental benefits of AAC are associated with the possibility of ensuring the highest content of by-products and production wastes, such as slag, fly ash, red mud, etc. [6]. Possibility of utilization of industrial wastewater in production of safe building materials on AAC basis has also been shown [7].…”
Section: Introductionmentioning
confidence: 97%
“…Environmental benefits of AAC are associated with the possibility of ensuring the highest content of by-products and production wastes, such as slag, fly ash, red mud, etc. [6]. Possibility of utilization of industrial wastewater in production of safe building materials on AAC basis has also been shown [7].…”
Section: Introductionmentioning
confidence: 97%
“…It is shown that combining super-zeolite (SZ) and separated fly ash (SFA) can reduce power consumption for the preparation of highly active SCMs up to 31 kWh/tonne. Another idea comes from [29] on designing an alternative alkali-activated Portland cement by using a mineral additive of granulated blast furnace slag and fly ash. The aim of the research is to accomplish the blended cement composition, in which the hydrated products can reach a higher strength than 40 MPa.…”
Section: Discussion Of the Results Of The Testing And Characterization Of The Alternative Low-energy Bindersmentioning
confidence: 99%
“…-minimizing the expansion effect is achieved by introducing various active mineral additives to the cement composition. These additives can be both of secondary [17] and volcanic origin (limestone with amorphous silica content [18], zeolites [19], perlite, tuff, etc. [20]).…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%